Melitourism Potential of Bali, Indonesia and Bicol, Philippines - Nicolas, Amelia; Hidalgo, Hanilyn; Fresnido, Mia Bella; Mangku, I Gede Pasek; Udayana, I Gusti Bagus (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2022)
Melitourism, a special entomotourism featuring stingless bees as an agritourism attraction, remains less popular and underrated in Southeast Asian countries despite its economic benefits. This study assessed the melitourism potential of Bali, Indonesia, and Bicol, Philippines, through a qualitative approach using various indicators such as financial capital, market, social capital, environment, technology, policy, human capital, culture, and farm tourism as foundations for a melitourism social enterprise. Identification of these indicators was based on a literature review, and these became the basis of an interview guide designed for stingless bee operators. Findings showed that meliponiculture in Bali and Bicol offers a lot of promise as a social enterprise and tourism development. The stingless beekeeping industry dominated the aspects of environmental, technological, market, and social capital. Farmer groups provide a support system resulting in strong social capital. Compared to Bali, Bicol is quite advanced in agritourism integration in stingless bee farms. Melitourism is a good means of engaging the public to contribute towards a conducive entrepreneurial ecosystem for stingless beekeeping. Incorporating the tourism aspect in meliponiculture is a good economic diversification strategy that would enhance farm productivity and encourage farmers to engage in ethical practices that help maintain a healthy stingless bee population both on farms and in the wild. However, to hasten farmer engagement and melitourism development, local and national governments must strengthen their policy infrastructure and support this industry. Keywords— melitourism, entomotourism, stingless beekeeping, apitourism, meliponiculture.